Carboplatin and cisplatin ototoxicity in guinea pigs - Taudy, M; Syka, J; Popelár, J; Ulehlová, L (Audiology, 1992)
Ototoxic effects of cisplatin (1.5 mg/kg), cisplatin with mannitol (1.5 mg/kg cisplatin with 15 mg/kg mannitol) and carboplatin (6 mg/kg) were compared in guinea pigs treated 5 days a week for 5 consecutive weeks. Auditory thresholds were measured in awake animals by means of the compound action potential recorded from electrodes implanted near the round window. The endocochlear potential (EP) was measured in the first turn through the round window, and hair cell counts were estimated by the surface specimen technique. The most pronounced ototoxicity (threshold shifts and hair cell loss) was observed with pure cisplatin. Cisplatin with mannitol appeared to be less toxic than pure cisplatin, and carboplatin the least toxic. Even carboplatin produced significant threshold shifts, particularly at high frequencies, but they were not accompanied by hair cell loss. Values of EP were not different from those in normal control animals.
Keywords: Ear, Inner; Carboplatin; implantované elektrody; Guinea Pigs; Hearing; Auditory Threshold; Cochlea; Cisplatin; cisplatina; Electrodes, Implanted; injekce intraperitoneální; kochlea; sluchový práh; sluch; Drug Combinations; Mannitol; fixní kombinace léků; morčata; karboplatina; Hair Cells, Auditory; vnitřní ucho; Injections, Intraperitoneal; ženské pohlaví; zvířata; Acoustic Stimulation; mannitol; vláskové buňky; akustická stimulace; Female; Animals